BUILDING SOCIAL CAPITAL THROUGH INCLUSIVE BASKETBALL - S. Djobova; M. Borukova; I. Kirilova (Trakia Journal of Sciences)
The inclusive basketball program of the National Sports Academy is a compilation of adapted and unified basketball where persons with intellectual and physical disabilities together with students and volunteers are training and competing together. PURPOSE of this study is to explore the extent of contribution of our program for the building of social capital. The concept of social capital is drawn from psychology, sociology and economy. It is defined as controversial due to many theories and cultural diversity behind. METHODS: Participants in the study were all persons involved in the adapted basketball program. Data was collected using interviews, life-story techniques, field notes and tests batteries for basketball skills. RESULTS are showing improvement in personal development domain for the athletes with disabilities where sport specific skills, building trust and communications were the leading components. For the students in the same domain the leading components of improvement were attitudes and relationships. Positive change was found in the domains of social inclusion, micro-culture and participation. We also found that there is direct and indirect production of social capital. CONCLUSION: inclusive sport practice like our adapted basketball program could be considered as a powerful contributor to the building of social capital.